Bilateral en-masse distalization of maxillary posterior teeth with skeletal anchorage: a case report - Saeed Noorollahian; Shiva Alavi; Farinaz Shirban (Dental Press Journal of Orthodontics)
ABSTRACT Objective: The aim of this study was to introduce a new method for bilateral distal movement of the entire maxillary posterior segment. Case report: A 17-year-old girl with Class I skeletal malocclusion (end-to-end molar relationships, deviated midline and space deficiency for left maxillary canine) was referred for orthodontic treatment. She did not accept maxillary first premolars extraction. A modified Hyrax appliance (Dentaurum Ispringen, Germany) was used for bilateral distalization of maxillary posterior teeth simultaneously. Expansion vector was set anteroposteriorly. Posterior legs of Hyrax were welded to first maxillary molar bands. All posterior teeth on each side consolidated with a segment of 0.017 × 0.025-in stainless steel wire from the buccal side. Anterior legs of Hyrax were bent into eyelet form and attached to the anterior palate with two mini-screws (2 × 10 mm) (Jeil Medical Corporation Seoul, South Korea). Hyrax opening rate was 0.8 mm per month. Lateral cephalometric radiographs were used to evaluate the extent of distal movement. 3.5-mm distalization of posterior maxillary teeth was achieved in five months. Results: A nearly bodily distal movement without anchorage loss was obtained. Conclusion: The mini-screw-supported modified Hyrax appliance was found to be helpful for achieving en-masse distal movement of maxillary posterior teeth.